AI-Powered IoT System for Early Detection and Monitoring of Livestock Health - V.T. Krishnaprasath; Arsath Mohammed F; Haribalan C; Saravana KumarJ; Sunoj C H; Rajichellam J (International Journal of Electrical and Communication Engineering Technology, 2025)
Protection of food production exists through livestock farming operations that advance economic global power. Continuous challenges to agricultural industry practices result in harmed animal health and enable disease spread as well as environmental threats to their welfare. Implementing current innovative solutions right away is necessary to solve these problems. The AI and IoT-based smart livestock health monitoring system functions as the fundamental development approach across this industry. The present integrated solution includes automatic high-tech indicator data collection that allows real-time observation which activates notifications for farmers and veterinarians. The combination of sensors provides better AI analytics and remote solution performance to instantly detect health conditions thereby enabling farmers to make better decisions. The new system raises the quality of life for livestock owners since it improves productivity levels together with environmental sustainability goals. The system demonstrates potential for higher resource efficiency because its configurable design and multi-farm scalability improve operational performance on farms. The inventive system drives livestock management methods toward superior levels and creates sustainable flexible operational systems for agricultural environments. The system enables farmers to keep their animals healthy by receiving immediate health data through real-time predictions that prevent animal-related risks.
Keywords: Cloud System; IOT Devices; Livestock; Machine Learning; Real time analysis; health monitoring